Recommendations of the Thoracic Imaging Section of the German Radiological Society for clinical application of chest imaging and structured CT reporting in the COVID-19 pandemic - Vogel-Claussen, Jens; Ley-Zaporozhan, Julia; Agarwal, Prerana; Biederer, Jürgen; Kauczor, Hans-Ulrich; Ley, Sebastian; Kühl, Hilmar; Mueller-Lisse, Ullrich G.; Persigehl, Thorsten; Schlett, Christopher L.; Wormanns, Dag; Antoch, Gerald; Hamer, Okka W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
This information provided by the Thoracic Imaging Section of the German Radiological Society is intended to give physicians recommendations on the use of thoracic imaging procedures in the context of the current COVID-19 pandemic. It represents the consensus of the authors based on the previous scientific knowledge and is intended to provide guidance for unified, structured CT reporting if COVID-19 pneumonia is suspected. The recommendations presented correspond to state of knowledge at the time of print and will be updated according to the results of ongoing and future scientific studies.Key Points:Citation FormatDiese Information der AG Thoraxdiagnostik der Deutschen Röntgengesellschaft soll Ärztinnen und Ärzten Empfehlungen zur Anwendung thoraxradiologischer Verfahren im Rahmen der aktuellen COVID-19-Pandemie geben. Sie repräsentiert den Konsensus der Autoren basierend auf den bisherigen wissenschaftlichen Erkenntnissen und soll zur einheitlichen und strukturierten CT-Befundung bei COVID-19 anleiten. Die vorgestellten Empfehlungen entsprechen dem Wissensstand zum Zeitpunkt der Drucklegung und werden entsprechend den Ergebnissen laufender und zukünftiger wissenschaftlicher Untersuchungen bei Bedarf aktualisiert.Kernaussagen:Zitierweise
Keywords: lung; COVID-19; imaging; German Radiological Society